Modern Approaches to Treating Multiple Osteogenic Metastases (Literature Review) - Rakhimov Nodir Makhmamatkulovich; Shahanova, Shakhnoza Shavkatovna; Davronov Eshboy Egamkulovich; Mirzakulov Bunyod Gaybullayevich; Murodov Shakhzod Tokhir ugli (Scholars Digest Publishing, 2023)
Early detection of bone metastases is crucial in reducing morbidity and improving outcomes. However, current imaging methods, such as bone scintigraphy, have limitations in sensitivity, while whole-body MRI may be limited in accessibility and cost. Existing standards only recommend imaging when symptoms, such as bone pain or fractures, are present, thereby limiting the diagnosis of patients with debilitating or complicating metastases. In the absence of appropriate methods, adequate monitoring with clinical observation becomes essential in managing patients with multiple osteogenic metastases.
Keywords: multiple osteogenic metastases, X-rays, bone.